The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/mnm.0000000000000750
|View full text |Cite
|
Sign up to set email alerts
|

Occipital lobe and posterior cingulate perfusion in the prediction of dementia with Lewy body pathology in a clinical sample

Abstract: The combination of medial and lateral occipital hypoperfusion with preserved posterior cingulate gyrus perfusion is highly specific for individuals with a positive I-FP-CIT scan in a clinical sample where diagnostic doubt exists. This regional combination, however, lacks sensitivity; therefore, absence of the sign cannot be used to rule out dementia with Lewy bodies. A positive finding provides strong evidence to rule in dementia with Lewy bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Interestingly, there was no significant global PVS volume fraction difference between IPD and FPD; however, there was a significantly higher regional PVS volume fraction in the white matter of the lateral occipital and cuneus regions in IPD compared to FPD. Both brain regions have been implicated in PD‐related cognitive impairment through changes in perfusion and volume in the lateral occipital and cuneus regions, respectively 64,72 . Despite these observed differences, the clinical distinction between IPD and FPD remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there was no significant global PVS volume fraction difference between IPD and FPD; however, there was a significantly higher regional PVS volume fraction in the white matter of the lateral occipital and cuneus regions in IPD compared to FPD. Both brain regions have been implicated in PD‐related cognitive impairment through changes in perfusion and volume in the lateral occipital and cuneus regions, respectively 64,72 . Despite these observed differences, the clinical distinction between IPD and FPD remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Both brain regions have been implicated in PD-related cognitive impairment through changes in perfusion and volume in the lateral occipital and cuneus regions, respectively. 64,72 Despite these observed differences, the clinical distinction between IPD and FPD remains unclear. Some reports indicate greater cognitive deficits and/or progression in familial forms such as SNCA and GBA, 73,74 whereas others show the opposite [75][76][77] or no clinical differences.…”
Section: Discussionmentioning
confidence: 99%
“…The occipital lobe is important for visuospatial processing. Hypoperfusion and atrophy in the occipital lobe has been associated with dementia with Lewy bodies ( Hanyu et al, 2006 ; Prosser et al, 2017 ), visual hallucinations in Alzheimer’s disease ( Holroyd et al, 2000 ), and poor cognitive scores ( Smith et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cingulate hypometabolism was also found to be missed frequently in patients meeting clinical criteria for DLB, and significant disagreement existed between radiological reports and independent reads. Classically, the cingulate island sign, identified as sparing of metabolism in the posterior cingulate region as compared to the precuneus and cuneus, was identified as a specific marker when taken alongside occipital hypometabolism [ 11 , 12 ]. Other studies found that the degree of cingulate hypometabolism in the presence of occipital hypometabolism may correlate to coexisting AD pathology as well [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other regions of interest have been identified in DLB, such as preservation of posterior cingulate island perfusion, which can enhance specificity for DLB on FDG-PET studies up to 100% when taken alongside occipital hypometabolism concurrently [ 10 ]. Prosser et al [ 11 ] found that preserved cingulate island perfusion and reduced occipital hypometabolism on Tc-HMPAO SPECT increase specificity but not sensitivity for DLB. Conversely, another study by Graff-Radford et al [ 12 ] found that the degree of cingulate island metabolism was inversely correlated with Braak Neurofibrilary Tangle (NFT) staging, suggesting coexistence of Alzheimer Disease pathology in patients carrying a diagnosis of probable DLB and exhibiting cingulate hypoperfusion.…”
Section: Introductionmentioning
confidence: 99%